A post-mortem study of gastric and duodenal peptic lesions: Part I Frequency and distribution by age and sex. Issue 4 (December 1963) - Levij, I. S.; De La Fuente, A. A.
Abstract : The overall incidence of peptic lesions in the reported series was 24·3%. Chronic peptic lesions were much higher in males (22·9%) than in females (12·2%). The incidence in males increased gradually from 19·6% in 1940-43 to 26·5% in 1956-58; in females there was an increase in the last few years only. Acute peptic lesions were approximately of the same incidence in males (6·3%) and in females (5·6%). In both sexes there was a sudden increase in frequency after 1949. Correlations have been demonstrated between acute peptic lesions and acute pathological conditions of the central nervous system, and between both acute and chronic lesions and chronic pulmonary diseases.